Accounting for Institutional Work: A Critical Review. Issue 1 (1st January 2022) - Modell, Sven
Abstract : This paper offers a review of a rapidly growing body of accounting research, using the concept of institutional work, with an eye to whether and how it has addressed key criticisms levied at this strand of institutional theory. Four sets of criticism of the institutional work perspective, pivoting on its emphasis on such work as an institutionally embedded multi-level phenomenon, the intentions behind institutional work, the relationship between habitual and reflexive agency and its conception of power, are identified. Insofar as accounting research using the concept of institutional work has addressed such criticisms, it has mainly been confined to those emerging within institutional theory whilst much less attention has been paid to criticisms raised by critical management scholars who are less sympathetic to institutional theory. Drawing on recent advances in critical sociology, I advance a framework that addresses these criticisms. In doing so, I discuss the possibilities of imbuing research on institutional work with innate concerns with radical social critique and emancipation. This contributes to a refined understanding of institutional work as a source of change and stability and provides a platform for turning institutional accounting research into a politically engaged research program underpinned by critical intent.